Modelagem da circulação atmosférica na região da usina termoelétrica de Candiota - Alves, Rita de Cássia Marques; Dias, Maria Assunção Faus da Silva; Moraes, Osvaldo Luiz Leal de (Ciência e Natura, 2000)
In this paper it is used the Regional Atmospheric Modeling System (RAMS) in order to simulate the atmospheric circulation around the Candiota Thermoelectric Power Plant. Two numerical experiments are showed. The first one describes the sensitivity of the model to the local topography. In the second one the model is initialized with data from CPTEC/INPE and the results are compared with data obtained in fields campaigns. This comparison indicates that the RAMS outputs are an useful tools to be used in atmospheric dispersion models to describe the pollutant transport emitted by the Candiota source.